2021
DOI: 10.1371/journal.pone.0255077
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder predicts poor health-related quality of life in cardiac patients in Palestine

Abstract: Background The longitudinal association of posttraumatic stress disorder (PTSD) with health-related quality of life (HRQL) in cardiac patients’ remains poorly studied, particularly in conflict-affected settings. Materials and methods For this cohort study, we used baseline and one-year follow-up data collected from patients 30 to 80 years old consecutively admitted with a cardiac diagnosis to four major hospitals in Nablus, Palestine. All subjects were screened for PTSD and HRQL using the PTSD Checklist Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Relevant data also show that loneliness, irritability, irritability, fear, depression, anxiety, pessimism, despair, and other adverse psychological problems affected the quality of life of cancer patients with the disease and could cause a vicious cycle between adverse psychology and pathophysiology [21]. In addition, after the occurrence of posttraumatic stress disorder, patients may have flashbacks and recurrence of traumatic memories, avoidance, and hypervigilance, which affected their quality of life [22,23]. Enabling psychological nursing took the patient as the center, according to the real idea of the patients' heart, to take targeted psychological counseling, so that the patients have a healthy and positive psychology, so as to improve the quality of life [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant data also show that loneliness, irritability, irritability, fear, depression, anxiety, pessimism, despair, and other adverse psychological problems affected the quality of life of cancer patients with the disease and could cause a vicious cycle between adverse psychology and pathophysiology [21]. In addition, after the occurrence of posttraumatic stress disorder, patients may have flashbacks and recurrence of traumatic memories, avoidance, and hypervigilance, which affected their quality of life [22,23]. Enabling psychological nursing took the patient as the center, according to the real idea of the patients' heart, to take targeted psychological counseling, so that the patients have a healthy and positive psychology, so as to improve the quality of life [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with what occurs in the Palestinian context, as Palestinins people face challenging living conditions due to the ongoing military occupation that is considered a risk factor for individuals' low quality of life and psychological well-being. Allabad et al 33 tested the role of stressful life events in predicting poor health-related quality of life among Palestinians; the results revealed that individuals with depression or anxiety potentially face poor health-related quality of life. Massad et al 34 examined the correlation between health-related quality of life, trauma, stress, and depression in another study.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a shortage of instruments specific to the Palestinian region for determining traumatic symptoms. For example, in a study that explored the longitudinal association of PTSD with health-related quality of life in cardiac patients particularly in conflict-affected settings, the researchers used the PTSD Checklist Specific (PCL-S) to assess PTSD (Allabadi et al, 2021). To examine the relationship between siege stressors, war trauma and PTSD among Palestinian women in the Gaza Strip, PCL (DSM-IV) (Arabic version) was used (Aqel and Thabet, 2018).…”
Section: Introductionmentioning
confidence: 99%